Role of freshwater availability and terrestrial land‐cover change in the distribution of a declining, terrestrial, insectivorous bird - Catrin F. Eden; Simon Gillings; Richard K. Broughton; Bart Donato; Chris M. Hewson; Stuart P. Sharp (Conservation Biology, 2026)
Insectivorous, Afro‐Palearctic migrant birds provide cross‐border ecosystem services, but many are declining rapidly. The complex life cycle of migrant birds makes their conservation difficult, but understanding where they spend time during the breeding season can help indicate where those actions will be most effective. We used the spotted flycatcher ( Muscicapa striata ), a declining, Afro‐Palearctic, migratory insectivore and habitat generalist, as a model to examine how river density and land‐cover change were associated with loss and colonization during the breeding season of 2 × 2‐km national atlas survey areas from 1990 to 2010. Greater river density was associated with a lower probability of loss (odds ratio [OR] 0.8) between survey periods and a higher probability of colonization (OR 1.25). Loss was associated with increases in urban land cover (OR 1.17), and, unexpectedly, colonization was negatively associated with increases in woodland (OR 0.91) and standing freshwater (OR 0.94). Our results suggest that habitat creation is unlikely to provide sufficient benefits for some insectivorous birds within the time needed for population recovery. Thus, efforts should focus on the protection and improvement of established habitats. River density was strongly associated with the persistence of the spotted flycatcher, and this finding highlights that understanding the benefits of freshwater habitat for terrestrial species should be a priority for conservation management.

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Cross-system transfer of fatty acids from aquatic insects supports terrestrial insectivore condition and reproductive success - Catrin F. Eden; Richard K. Broughton; Bart Donato; Chris M. Hewson; Caroline Isaksson; Stuart P. Sharp (Oecologia, 2025)
Cross-system fluxes of aquatic insects rich in omega-3 long-chain polyunsaturated fatty acids (ω-3 LC-PUFAs), specifically eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), may subsidise insectivorous vertebrates that are suffering due to terrestrial insect declines. The benefits of high ω-3 LC-PUFA diets, such as improved growth and immunocompetence, have previously been demonstrated for riparian insectivores. Understanding the potential for aquatic insects to benefit a range of species is necessary for informing land management practices. Using the spotted flycatcher ( Muscicapa striata ), a habitat-generalist, insectivorous bird as a model, we tested how blood plasma ω-3 LC-PUFA concentrations and the ratio of ω-6:ω-3 fatty acids were related to the body condition of 14 adults and 84 chicks in the wild. We measured how variation in ω-3 LC-PUFAs and ω-6:ω-3 was related to river proximity, to test whether they were related to aquatic insect availability. We assessed how these relationships may extend beyond the individual level by monitoring flying insect availability throughout two breeding seasons and testing its ability to predict reproductive success. EPA was positively correlated with body condition in chicks and adults and declined with distance from a river. Conversely, ω-6:ω-3 was negatively correlated with body condition and increased with distance from a river. Breeding success was positively correlated with aquatic insect availability, suggesting that access to a high ω-3 LC-PUFA diet has the potential to mitigate declines in generalist insectivores. Our results highlight how the maintenance or creation of high-quality freshwater habitats may be promoted in a conservation context for non-riparian species.

Assimilatory processes dominate diel inorganic nitrogen cycling in a shallow open-water constructed wetland - Richard L. Smith; Ariel P. Reed; Deborah A. Repert; Craig R. Tobias; Jonathan O. Sharp (Science of The Total Environment, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Moche chronology of ancient Peru: Bayesian assessment of radiocarbon dates and ceramic styles from north to south - Michele L. Koons; Branden Cesare Rizzuto; Lisa Trever; Alicia Boswell; Augusto Bazán Pérez; Luis A. Muro Ynoñán; Gabriel Prieto; Carlos Rengifo; Kayeleigh Sharp; Edward Swenson; Hugo Ikehara-Tsukayama; Jessica Ortiz Zevallos; et al. (Quaternary International, 2024)

Leveraging satellite observations to reveal ecological drivers of pest densities across landscapes - Sara E. Emery; Jay A. Rosenheim; Rebecca Chaplin-Kramer; Richard Sharp; Daniel S. Karp (Science of The Total Environment, 2024)

Feasibility and acceptability of an acceptance-based guided self-help programme for weight loss maintenance - Julia Mueller; Rebecca A. Jones; Rebecca Richards; Jennifer Woolston; Fiona Whittle; Andrew J. Hill; Carly A. Hughes; Robbie Duschinsky; Stephen J. Sharp; Clare Boothby; Jennifer Bostock; Penny Breeze; et al. (Appetite, 2023)

Conservation genomics of an exploited, popular aquarium trade species: the giant Caribbean sea anemone Condylactis gigantea (Anthozoa: Actiniidae) - Nancy E. Sheridan; Seifu Seyoum; William C. Sharp; Benjamin M. Titus; Marymegan Daly; Christina L. Richards; Aaron W. Schrey (Conservation Genetics, 2023)

PMEL’s Contribution to Observing and Analyzing Decadal Global Ocean Changes Through Sustained Repeat Hydrography - Zachary Erickson; Brendan Carter; Richard Feely; Gregory Johnson; Jonathan Sharp; Rolf Sonnerup (Oceanography, 2023)
The ocean is warming, acidifying, and losing oxygen. The Global Ocean Ship-based Hydrographic Investigations Program (GO-SHIP) carries out repeat hydrographic surveys along specified transects throughout all ocean basins to allow accurate and precise quantification of changes in variables such as temperature, salinity, carbon, oxygen, nutrients, velocity, and anthropogenic tracers, and uses these observations to understand ventilation patterns, deoxygenation, heat uptake, ocean carbon content, and changes in circulation. GO-SHIP provides global, full-depth, gold-standard data for model validation and calibration of autonomous sensors, including Argo. The Pacific Marine Environmental Laboratory, through sustained funding from NOAA, has developed methods to measure several of the variables routinely sampled through GO-SHIP and is a core contributor to these repeat hydrographic cruises.

Reproductive factors and the risk of breast cancer among Nigerian women by age and oestrogen receptor status - Samuel O. Azubuike; Louise Hayes; Linda Sharp; Richard McNally (Cancer Causes & Control, 2022)

Use of multiple endpoints to assess the impact of captivity on gut flora diversity in Long Island Sound Fundulus heteroclitus - Joseph P. Battaglia; Christian M. Kearney; Kirsten Guerette; Jordan Corbishley; Emily Sanchez; Brennah Kent; Hanna Storie; Emma Sharp; Shane Martin; Matthew Saberito; Jonathan D. Blake; Richard S. Feinn; et al. (Environmental Biology of Fishes, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Development and molecular cytogenetic characterization of Thinopyrum bessarabicum introgression lines in hexaploid and tetraploid wheats - Amit K. Singh; Peng Zhang; Chongmei Dong; Jianbo Li; Smriti Singh; Richard M. Trethowan; Peter J. Sharp (Theoretical and Applied Genetics, 2020)

Reference points for predators will progress ecosystem‐based management of fisheries - Simeon L. Hill; Jefferson Hinke; Sophie Bertrand; Lowell Fritz; Robert W. Furness; James N. Ianelli; Matthew Murphy; Ricardo Oliveros‐Ramos; Lorien Pichegru; Rowland Sharp; Richard A. Stillman; Peter J. Wright; et al. (Fish and Fisheries, 2020)
Ecosystem‐based management of fisheries aims to allow sustainable use of fished stocks while keeping impacts upon ecosystems within safe ecological limits. Both the FAO Code of Conduct for Responsible Fisheries and the Aichi Biodiversity Targets promote these aims. We evaluate implementation of ecosystem‐based management in six case‐study fisheries in which potential indirect impacts upon bird or mammal predators of fished stocks are well publicized and well studied. In particular, we consider the components needed to enable management strategies to respond to information from predator monitoring. Although such information is available in all case‐studies, only one has a reference point defining safe ecological limits for predators and none has a method to adjust fishing activities in response to estimates of the state of the predator population. Reference points for predators have been developed outside the fisheries management context, but adoption by fisheries managers is hindered a lack of clarity about management objectives and uncertainty about how fishing affects predator dynamics. This also hinders the development of adjustment methods because these generally require information on the state of ecosystem variables relative to reference points. Nonetheless, most of the case‐studies include precautionary measures to limit impacts on predators. These measures are not used tactically and therefore risk excessive restrictions on sustainable use. Adoption of predator reference points to inform tactical adjustment of precautionary measures would be an appropriate next step towards ecosystem‐based management.

Methanogenic potential of Arctic and Antarctic subglacial environments with contrasting organic carbon sources - Marek Stibal; Jemma L. Wadham; Grzegorz P. Lis; Jon Telling; Richard D. Pancost; Ashley Dubnick; Martin J. Sharp; Emily C. Lawson; Catriona E. H. Butler; Fariha Hasan; Martyn Tranter; Alexandre M. Anesio (Global Change Biology, 2012)
Subglacial environments are largely anoxic, contain organic carbon ( OC ) overridden by glacier ice during periods of advance, and harbour active microbial communities. This creates favourable conditions for OC degradation via methanogenesis. It has been hypothesized that OC beneath ice sheets is converted to methane ( CH 4 ) and may be released to the atmosphere during retreat. However, there are limited data available to support this contention. Here, we present new data on the abundance, diversity and activity of methanogenic archaea and the amount and character of OC in subglacial sediments from Arctic and Antarctic glacial systems based on different substrate types. We employed long‐term laboratory incubations to quantify the CH 4 production potential in different subglacial settings. Significant numbers of methanogens (up to 7 × 10 4 cells g −1 ) were detected in the samples and clones of Methanomicrobiales and Methanosarcinales were identified in clone libraries. Long lag periods (up to >200 days) were observed before significant CH 4 concentrations were measured. We report order of magnitude differences in rates of CH 4 production (10 1 –10 5 fmol g −1 d −1 ) in different subglacial sediments, reflecting contrasts in the origin of the sediment and the OC character. Hence, we predict that contrasting rates of CH 4 production are likely to occur beneath glaciers and ice sheets that overran different types of substrate. We subsequently estimated the potential for CH 4 production beneath the Laurentide/Inuitian/Cordilleran and Fennoscandian Ice Sheets during a typical 85 ka Quaternary glacial/interglacial cycle. CH 4 production from lacustrine‐derived OC is likely to be an order of magnitude higher (~6.3–27 Pg C) than that from overridden soils (~0.55–0.68 Pg C), possibly due to a difference in lability between lacustrine and soil OC . While representing a fraction of the entire OC pool (~418–610 Pg C), this finding highlights the importance of considering the character of different OC pools when calculating subglacial CH 4 production.

Influence of age, sex, and aerobic capacity on forearm and skin blood flow and vascular conductance - Gary J. Hodges; Lisa Sharp; Richard E. Clements; David F. Goldspink; Keith P. George; Nigel T. Cable (European Journal of Applied Physiology, 2010)

The Environmental Polymorphisms Registry: a DNA resource to study genetic susceptibility loci - Patricia C. Chulada; Heather L. Vahdat; Richard R. Sharp; Tracy C. DeLozier; Paul B. Watkins; Susan N. Pusek; Perry J. Blackshear (Human Genetics, 2008)

Dopamine agonists disrupt visual latent inhibition in normal males using a within-subject paradigm - Neal R. Swerdlow; Nora Stephany; Lindsay C. Wasserman; Jo Talledo; Richard Sharp; Pamela P. Auerbach (Psychopharmacology, 2003)

Comparative study of the thermostabilizing properties of mannosylglycerate and other compatible solutes on model enzymes - Nuno Borges; Ana Ramos; Neil Raven; Richard Sharp; Helena Santos (Extremophiles, 2002)

Comparison of microbial populations in model and natural rumens using 16S ribosomal RNA‐targeted probes - Cherie J. Ziemer; Richard Sharp; Marshall D. Stern; Michael A. Cotta; Terence R. Whitehead; David A. Stahl (Environmental Microbiology, 2000)
A model rumen system, dual‐flow continuous culture fermenters, was evaluated by two comparative criteria in two experiments using ribosomal (r)RNA‐targeted DNA probes to compare key microbial groups in samples. The initial experiment measured temporal changes in population structure during adaptation of ruminal microbial populations in fermenters over 240 h. The fermenter inoculum contained 34.9% Bacteria, 60.1% Eukarya and 6.8% Archaea measured as a fraction of total small subunit (SSU) rRNA quantified using a universal probe. The cellulolytic bacterial genus Fibrobacter comprised 9.5% of total SSU rRNA in the inoculum. After 240 h of fermenter operation, the average abundance was 80.9% Bacteria, 6.1% Eukarya, 5.1% Archaea and Fibrobacter genus accounted for 6.6% of the total SSU rRNA. Divergence between ruminal and fermenter population structure was evaluated in the second experiment and samples were classified as ruminal, inoculum or fermenter (96, 120, 144 and 168 h of fermenter operation). Fermenter samples had higher relative abundances of Bacteria (84.5%) and Archaea (2.1%) and lower relative abundances of Eukarya (1.8%) than ruminal samples (average 48.0% Bacteria, 1.3% Archaea and 61.5% Eukarya). The relative abundance of Fibrobacter was similar in all samples, averaging 2.5%. The ruminal and fermenter samples had similar proportions of F. succinogenes and F. succinogenes subgroup 3 (as a percentage of Fibrobacter SSU rRNA). Fibrobacter succinogenes subgroup 1 and F. intestinalis proportions of Fibrobacter were lower in fermenter samples (8.2% and 0.7% respectively) than in ruminal samples (28.4% and 2.2% respectively). Fermenters were able to maintain a core prokaryotic community structure similar to the native microbial community in the rumen. Although protozoa populations were lost, maintenance of Fibrobacter and archaeal populations indicated that the model system supported a functional community structure similar to the rumen. This model rumen system may serve as a suitable tool for studying aspects of ruminal microbial ecology and may resolve some of the relationships between microbial community structure and function by providing control of experimental conditions.

A microbiological survey of Montserrat Island hydrothermal biotopes - Tony Atkinson; Steven Cairns; D. A. Cowan; Michael J. Danson; David W. Hough; D. Barrie Johnson; Paul R. Norris; Neil Raven; Clare Robinson; Rob Robson; Richard J. Sharp (Extremophiles, 2000)

Influence of Gravity on Cardiac Performance - George M. Pantalos; M. Keith Sharp; Stewart J. Woodruff; D. Sean O’Leary; Richard Lorange; Scott D. Everett; Thomas E. Bennett; Thomas Shurfranz (Annals of Biomedical Engineering, 1998)

A polyphasic taxonomic study of thermophilic bacilli from a wide geographical area - Duncan White; Richard J. Sharp; Fergus G. Priest (Antonie van Leeuwenhoek, 1994)